Towards Teleneuropsychology Training: Insights from Australian Clinical Neuropsychology Trainees and Supervisors - Dominic J. Giuliano; Brittany Wolff; Nicola Marie Chalet; Ningjing Cui; Wendy Kelso; Renerus J. Stolwyk (Journal of Technology in Behavioral Science, 2026)
Abstract Clinical neuropsychology training institutions face the challenge of providing up-to-date instruction on rapidly evolving healthcare innovations, including teleneuropsychology (teleNP). This study explored the training needs, priorities, and preferences of Australian clinical neuropsychology trainees and supervisors to inform future training. An exploratory qualitative design was employed. Semi-structured interviews were conducted with 13 postgraduate neuropsychology trainees and 11 supervisors. Data were analyzed using reflexive thematic analysis. Four broad themes and four subthemes were generated: (1) initial disruption evolved into confidence with practice; (2a) knowledge and skill gaps and (2b) practice considerations; (3) building competence through structured learning and practice resources; (4a) teleNP training needs and (4b) competencies. In early-stage teleNP implementation, a lack of formal training led to high levels of anxiety which interfered with learning. Adjustment was supported by a collaborative “learning together” process that leveraged the variable technical and clinical skills of each party. Trainees sought observational and practical learning, while supervisors provided scaffolded training, progressing from foundational skills to simulated teleNP practice. Overall, both groups believed teleNP training should be embedded within postgraduate training. Seven training considerations and 11 teleNP competencies are proposed, derived through integration with the extant literature, to guide future implementation. The findings support the need for structured, competency-based teleNP training to be embedded early within clinical neuropsychology education. Such training aligns with emerging competency frameworks, prepares trainees to provide safe, ethical services, and supports efforts to improve healthcare access.